Analisis Perancangan Panel Surya Portabel Dengan Autotracking - Pangaribuan, Timbang; Manihuruk , Jonner; Hasiholan Pardosi , Cristoni; Hutauruk , Juniardo (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2023)
The world uses all resources to meet daily electrical energy needs so that shortly, we will run out of ore/mineral/petroleum, a source of electrical energy. As a result, renewable energy solutions have reached the current great demand to save natural resources and solve the energy crisis. Solar energy is rapidly gaining notoriety as an essential means of expanding renewable energy resources. Solar panels are devices that cleanly convert sunlight into electricity and offer a practical solution to the problem of generating electricity in remote areas. Therefore, it is significant for those of us in electrical engineering to understand the technology associated with this field. The solar panel system must be maximized to make solar energy more feasible and efficient than fossil energy. An automatic sun position tracking or solar tracker is a viable approach to optimizing the efficiency of a solar panel system. A solar tracker is a system that controls the movement of solar panels so that they are always aligned with the sun's position. The solar tracker uses a dual-axis system to align the solar panels with the sun's position. By using a solar tracker, it is expected that the solar panel system will produce maximum output power.